Industrial applications of biopolymers and their environmental impact - Al Mamun, Abdullah; Chen, Jonathan Y. (Boca Raton : CRC Press, 2019)
Biopolymers represent a carbon emission solution: they are green and eco-friendly with a variety of uses in biomedical engineering, the automotive industry, the packaging and paper industries, and for the development of new building materials. This book describes the various raw materials of biopolymers and their chemical and physical properties, the polymerization process, and the chemical structure and properties of biopolymers. Furthermore, this book identifies the drawbacks of biopolymers and how to overcome them through modification methods to enhance the compatibility, flexibility, physicochemical properties, thermal stability, impact response, and rigidity.
Modification of Polylactic Acid (PLA) and its Industrial Applications A. Al-Mamun, M. Nikusahle, M. Feldmann and H.-P. Heim Grain Waste Product as Potential Bio-fiber Resources A. Al-Mamun Bio-based Polyamides M. Feldmann PHB Production, Properties, and Applications M.A.K.M. Zahari, M.D.H. Beg, N. Abdullah and N.D. Al-Jbour Polyvinyl Alcohol and Polyvinyl Acetate Mohammad S. Islam Starch and Starch-based Polymers J. Fuchs and H.-P. Heim Chemistry of Cellulose M.D.H Beg, K. Najwa and J.O. Akindoyo Chitin and Chitosan and Their Polymers Md. Saifur Rahaman, Jahid M.M. Islam, Md. Serajum Manir, Md. Rabiul Islam and Mubarak A. Khan Carrageenan: A Novel and Future Biopolymer F. Adam, Md. A. Hamdan and S.H. Abu Bakar Natural Rubber and Bio-based Thermoplastic Elastomer Wei Jiang A Life Cycle Assessment of Protein-based Bioplastics for Food Packaging Applications A. Jones, S. Sharma and S. Mani Bio-polyurethane and Others M.A. Sawpan Keratin-based Bioplastic from Chicken Feathers: Synthesis, Properties and Applications A. Gupta, B.Y. Alashwal, Md. S. Bala and N. Ramakrishnan
OCLC-licensed vendor bibliographic record.
Keywords: Biopolymers -- Industrial applications; SCIENCE / Life Sciences / General; TECHNOLOGY / Engineering / Chemical & Biochemical